1995
DOI: 10.2307/2963498
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fire Regime and Habitat on Tree Dynamics in North Florida Longleaf Pine Savannas

Abstract: Frequent, low intensity fire was an important component of the natural disturbance regime of presettlement savannas and woodlands in the southeastern USA dominated by longleaf pine (Pinus palustris), and prescribed burning is now a critical part of the management of these endangered habitats. Fire season, fire frequency, and fire intensity are three potentially important, though still little understood, components of both natural and managed fire regimes. In this long—term (8—yr) study, we experimentally (thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
278
2
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 337 publications
(301 citation statements)
references
References 77 publications
(74 reference statements)
16
278
2
1
Order By: Relevance
“…In contrast, Glitzenstein, Streng, and Platt (1990) reported that longleaf pine mortahty, growth, and recruitment each did not differ significantly between plots burned in the growing season (April-August) and plots bmned in the dor-ERDC/CERLTR-03-13 15 mant season (October-February). Glitzenstein, Platt, and Streng (1995) gave supporting evidence that season of bum does not influence longleaf pine populations. Brockway and Lewis (1997) reported the lengthiest study of the effects of fire on longleaf pine.…”
Section: Effects Of Fire On Woody Vegetationmentioning
confidence: 84%
See 2 more Smart Citations
“…In contrast, Glitzenstein, Streng, and Platt (1990) reported that longleaf pine mortahty, growth, and recruitment each did not differ significantly between plots burned in the growing season (April-August) and plots bmned in the dor-ERDC/CERLTR-03-13 15 mant season (October-February). Glitzenstein, Platt, and Streng (1995) gave supporting evidence that season of bum does not influence longleaf pine populations. Brockway and Lewis (1997) reported the lengthiest study of the effects of fire on longleaf pine.…”
Section: Effects Of Fire On Woody Vegetationmentioning
confidence: 84%
“…Brose and Van Lear (1998) foimd that the density of oaks was positively influenced by both spring and winter bums, but growth rates were greater following winter bums. Glitzenstein, Streng, and Platt (1990) and GUtzenstein, Platt, and Streng (1995) foimd, however, that oak mortality was significantly greater after spring hvams (April, May) than bxmis in any other season. Oak recruitment was not affected by the season or frequency of burning, but growth was affected (GUtzenstein, Streng, and Platt 1990).…”
Section: Effects Of Fire On Woody Vegetationmentioning
confidence: 94%
See 1 more Smart Citation
“…An increase in woody species (shrubs and trees) also occurs in when fires are less frequent (Glitzenstein et al 2003). Dormant season fires also favor the increase of woody species (Glitzenstein et al 1995, Drewa et al 2002, Drewa et al 2006. The recent history of less frequent and more dormant season fires likely has resulted in increased woody cover in upland habitats such as dry prairie, pine flatwoods and sandhill.…”
Section: Continuity Of Fire Across Wetlandsmentioning
confidence: 99%
“…Our fire history focused on two important aspects of past fire regimes: fire frequency and intra-annual (or seasonal) timing of fire. Frequency is a very important aspect of fire regimes and differences in fire intervals over time may result in important differences in the structure and composition of biotic communities (Glitzenstein et al 1995(Glitzenstein et al , 2003. Likewise, the intra-annual timing of fire has important influences and many…”
Section: Introductionmentioning
confidence: 99%